High-density LD-based structural variations analysis in ten Native and Mestizo Mexican populations - Adriana Griselda Mateos-Valenzuela; Mirvana Elizabeth González-Macías; Carlos Villa-Angulo; Diana Helena Reyes-Godoy; Juan Carlos Fernandez-Lopez; Rafael Villa-Angulo (PLoS ONE, 2025)
The main objective of this study was to perform a genome-wide characterization of Structural Variations (SV) based on the deviation of the expected short-range Linkage Disequilibrium (LD) between Single Nucleotide Polymorphisms (SNPs) in 10 Native and Mestizo Mexican populations. We used a panel of 785,663 SNP genotypes, sampled from 383 individuals, of which 71 belonged to ethnic populations and 312 belonged to mestizo populations. The total number of variations found among all populations was 4,375, involving an average of 19,438 SNPs per population, which corresponds to the 3.14% of the total average of SNPs per population. The mean SV size varied from 2,845–8,646 kb across populations (with a mean SV size of 6,161 kb over all populations) and an average of 50.14 SNPs per SV. By grouping all variations across all populations in the sample we defined 506 regions, from which in 54 (11%) regions the 10 populations coincided. The total number of genes covered by these variations was 8,443. And, from all genes we identified some specifically related to Mexican health, as the genes FTO and ABCA1 associated with obesity, with the adipose tissue function, and with the distribution of fat in Mexican population; the gene ELMO1 associated with the susceptibility to diabetic nephropathy and diabetes type II, among others. In summary, our results add new evidence in support of the hypothesis that SVs based on the deviation of the expected short-range LD between SNPs capture the structure and the demographic history of populations, and represent potential targets for association of SVs with population-specific diseases.